Untangling the ATR‐CHEK1 network for prognostication, prediction and therapeutic target validation in breast cancer. Issue 3 (6th November 2014) - Abdel-Fatah, Tarek M.A.; Middleton, Fiona K.; Arora, Arvind; Agarwal, Devika; Chen, Tao; Moseley, Paul M.; Perry, Christina; Doherty, Rachel; Chan, Stephen; Green, Andrew R.; Rakha, Emad; Ball, Graham; et al.
Abstract : ATR‐CHEK1 signalling is critical for genomic stability. ATR‐CHEK1 signalling may be deregulated in breast cancer and have prognostic, predictive and therapeutic significance. We investigated ATR, CHEK1 and phosphorylated CHEK1 Ser345 protein (pCHEK1) levels in 1712 breast cancers. ATR and CHEK1 mRNA expression was evaluated in 1950 breast cancers. Pre‐clinically, biological consequences of ATR gene knock down or ATR inhibition by the small molecule inhibitor (VE‐821) were investigated in MCF7 and MDA‐MB‐231 breast cancer cell lines and in non‐tumorigenic breast epithelial cells (MCF10A). High ATR and high cytoplasmic pCHEK1 levels were significantly associated with higher tumour stage, higher mitotic index, pleomorphism and lymphovascular invasion. In univariate analyses, high ATR and high cytoplasmic pCHEK1 levels were associated with poor breast cancer specific survival (BCSS). In multivariate analysis, high ATR level remains an independent predictor of adverse outcome. At the mRNA level, high CHEK1 remains associated with aggressive phenotypes including lymph node positivity, high grade, Her‐2 overexpression, triple negative, aggressive molecular phenotypes and adverse BCSS. Pre‐clinically, CHEK1 phosphorylation at serine345 following replication stress was impaired in ATR knock down and in VE‐821 treated breast cancer cells. Doxycycline inducible knockdown of ATR suppressed growth, which was restored when ATR was re‐expressed. Similarly, VE‐821 treatment resulted in a dose dependent suppression of cancer cell growth and survival (MCF7 and MDA‐MB‐231) but was less toxic in non‐tumorigenic breast epithelial cells (MCF10A). We provide evidence that ATR and CHEK1 are promising biomarkers and rational drug targets for personalized therapy in breast cancer. Highlights: ATR‐CHEK1 pathway is critical for genomic stability. Deregulation of ATR‐CHEK1 network may influence breast cancer pathogenesis. High ATR protein is associated with aggressive phenotype and poor prognosis. High cytoplasmic CHEK1 is linked to aggressive breast cancer and poor prognosis. High CHEK1 mRNA is linked to aggressive breast cancer and poor prognosis.